External Beam Radiation Therapy (EBRT) and High-Dose-Rate (HDR) Brachytherapy for Intermediate and High-Risk Prostate Cancer: The Impact of EBRT Volume - Tharmalingam, Hannah; Tsang, Yatman; Choudhury, Ananya; Alonzi, Roberto; Wylie, James; Ahmed, Imtiaz; Henry, Ann; Heath, Catherine; Hoskin, Peter J. (International journal of radiation oncology, biology, physics, 2020)
Whole pelvis radiation therapy (WPRT) may improve clinical outcomes over prostate-only radiation therapy (PORT) in high-risk prostate cancer patients by sterilization of micrometastatic nodal disease, provided there is optimal control of the primary site. A prospective multicenter cohort study of eligible patients (stage ≥T2c, Gleason score ≥7 or presenting prostate-specific antigen ≥10) treated between 2009 and 2013 were enrolled in a United Kingdom national protocol delivering combined external beam radiation therapy and high-dose-rate brachytherapy. Centers elected to deliver WPRT, 46 Gy in 23 fractions or PORT 37.5 Gy in 15 fractions with 15 Gy single dose high-dose-rate brachytherapy. The primary endpoint was biochemical progression-free survival (bPFS). Secondary endpoints were overall survival, genitourinary, and gastrointestinal toxicity. This was not a randomized comparison and was subject to bias; the findings are therefore hypothesis generating, but not conclusive. Eight hundred and twelve patients were entered; 401 received WPRT and 411 received PORT. With a median follow-up of 4.7 years, 5-year bPFS rates for WPRT versus PORT arms were 89% versus 81% (P = .007) for all patients and 84% versus 77% (P = .001) for high-risk patients. Differences in bPFS remained significant after accounting for Gleason score, presenting prostate-specific antigen, T stage, and androgen deprivation therapy duration as covariates. There was no difference in overall survival. The overall post treatment toxicities across both cohorts were low with no greater than 1.5% of ≥grade 3 toxicities at any follow-up time point. WPRT increased both prevalence and cumulative incidence of acute genitourinary toxicity (P = .004) and acute gastrointestinal toxicity (P = .003). No difference in late radiation toxicity was observed. A significant improvement in 5-year bPFS was seen in intermediate and high-risk prostate cancer treated with WPRT compared with PORT in a combined external beam radiation therapy and brachytherapy schedule with no increase in late radiation toxicity.